Efektivitas Penurunan Tarif PPH Final Atas PHTB Pada Penerimaan Pajak Di KPP Cikarang Utara - BT, Muhammad Firdaus; Hidayati, Mainita (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
This study aims to provide a clear picture regarding the effectiveness of reducing final income tax rates for the transfer of land and building rights to tax receipts at the North Cikarang Tax Service Office (KPP). The type of research used descriptive qualitative research. Data collection was carried out using observation, interview, and documentation techniques. The data obtained was then analyzed qualitatively by studying the data, studying key words, writing down the 'model' found, and coding. The results of the study show that the effectiveness of reducing the final PPh rate on the transfer of land and building rights at KPP Pratama Cikarang Utara has been running effectively where when the policy was first implemented in 2016 there was an increase in reporting because there was an increase in land and building transfer transactions by the community or business entity. In practice, the amount of reporting has increased well even though in terms of tax revenue it has decreased. This shows the enthusiasm of taxpayers carrying out their obligations, in which case there is certainly an increase in compliance